Voxelwise analysis of diffusion MRI of cervical spinal cord using tract-based spatial statistics - Dostál, Marek; Keřkovský, Miloš; Staffa, Erik; Bednařík, Josef; Šprláková-Puková, Andrea; Mechl, Marek (Magnetic resonance imaging, 2020)
Robust voxelwise analysis using tract-based spatial statistics (TBSS) together with permutation statistical method is standardly used in analyzing diffusion tensor imaging (DTI) of brain. A similar analytical method could be useful when studying DTI of cervical spinal cord. Based on anatomical data of sixty-four healthy volunteers, white (WM) and gray matter (GM) masks were created and subsequently registered into DTI space. Using TBSS, two skeleton types were created (single line and dilated for WM as well as GM). From anatomical data, percentage rates of overlap were calculated for all skeletons in relation to WM and GM masks. Voxelwise analysis of fractional anisotropy values depending on age and sex was conducted. Correlation of fraction anisotropy values with age of subjects was also evaluated. The two WM skeleton types showed a high overlap rate with WM masks (~94%); GM skeletons showed lower rates (56% and 42%, respectively, for single line and dilated). WM and GM areas where fraction anisotropy values differ between sexes were identified (p < .05). Furthermore, using voxelwise analysis such WM voxels were identified where fraction anisotropy values differ depending on age (p < .05) and in these voxels linear dependence of fraction anisotropy and age (r = -0.57, p < .001) was confirmed by regression analysis. This dependence was not proven when using WM anatomical masks (r = -0.21, p = .10). The analytical approach presented shown to be useful for group analysis of DTI data for cervical spinal cord.
Keywords: dospělí; Healthy Volunteers; krční mícha; Female; Diffusion tensor imaging; Adult; ženské pohlaví; White Matter; difuzní magnetická rezonance; zdraví dobrovolníci pro lékařské studie; Anisotropy; lidé; Spinal cord; Cervical Cord; Algorithms; Male; počítačové zpracování obrazu; anizotropie; Diffusion Magnetic Resonance Imaging; algoritmy; Voxelwise analysis; lidé středního věku; mužské pohlaví; Middle Aged; bílá hmota; Image Processing, Computer-Assisted; Humans